If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-10=-5(u+9)
We move all terms to the left:
-10-(-5(u+9))=0
We calculate terms in parentheses: -(-5(u+9)), so:We get rid of parentheses
-5(u+9)
We multiply parentheses
-5u-45
Back to the equation:
-(-5u-45)
5u+45-10=0
We add all the numbers together, and all the variables
5u+35=0
We move all terms containing u to the left, all other terms to the right
5u=-35
u=-35/5
u=-7
| 18=6+3u | | 2.6=8.9=0.7x | | -5+x/5=-30 | | -5x+12=80 | | 2(u-3)-4u=4 | | 3x−2x+4=2+x+2 | | 6.4=-f | | -8w+6(w+5)=10 | | 2(x+4)=2x+82x+4=2x+8 | | 6x-2(7x+2)=44 | | 16z=-24=8(2z-3) | | -4+66=7n | | 10–3x–1=7+3x+2 | | -3(x-3)=-8x+39 | | -3.2b+5.6=13.8 | | 3/8n-1/1=5/6 | | 3=s−79 | | 3x+1=-(2-2x) | | d19=22 | | 3x+1=-( | | (x-3)^2=10 | | 816=8g | | b+11=54 | | -2/3(q=1/6)=-11/12 | | 2x+0=4x+1 | | 42-y=38-52 | | (-160/x^2)+0.1=0 | | x+34=2–12 | | 4-5p-15=9 | | 10y–2y=64 | | 4v-12=-2(v-2) | | X-34=2x-12 |